Application Research of Narrative Care to the Management of Symptom Clusters and Post-traumatic Growth in Patients Undergoing Lung Cancer Surgery - Xinxing SUN; Yalin WANG; Wang LV; Linhai ZHU (Chinese Journal of Lung Cancer)
Background and objective Narrative care is emerging as a new discipline to achieve high-quality nursing. It can be seen in clinical studies on improving the management of schizophrenia, depression and chronic diseases, but its application in surgical patients with lung cancer is rarely reported. The aim of this study was to study the effect on improving symptom cluster management and post-traumatic growth of surgical patients through narrative care model, and to explore its clinical advantages in promoting physical and mental rehabilitation of lung cancer patients. Methods A total of 82 patients with lung cancer who underwent surgical treatment in the First Affiliated Hospital of Zhejiang University from July 2024 to October 2024 were selected as the study objects by convenience sampling, and randomly divided into the control group and observation group according to random number method, with 41 cases in each group. The control group received routine nursing; On this basis, the observation group was integrated into three consecutive narrative nursing sessions on the day of admission, 3 days after surgery and 1 week after surgery. After collecting the general data of the patients before intervention, the Generalized Anxiety Scale, the Pittsburgh Sleep Quality Index, the Chinese Version of the Lung Cancer Patients Quality of Life Assessment Scale and the Chinese Version of the Post-traumatic Growth Assessment Scale were used. After each narrative intervention, the two groups of patients were assessed again, and the scores of the two groups were compared at the three stages. Results The scores of anxiety, sleep, quality of life and post-traumatic growth level of the patients on the 3 days and 1 week postoperatively were better in the observation group than in the control group, and the differences were all statistically significant (P<0.05). In addition, the results within the groups showed that the anxiety scores of the observation group and the control group gradually decreased in the preoperative period, 3 days and 1 week postoperatively; the post-traumatic growth scores gradually increased in the preoperative period, 3 days and 1 week postoperatively; however, due to the stress of the surgery and postoperative discomfort, the sleep scores of the patients of the two groups on 3 days postoperatively were higher than those in the preoperative period and 1 week postoperatively, and the sleep scores of the patients of 1 week postoperatively were significantly lower than those in the preoperative period; and the quality of life of the patients on the 3 days postoperatively scores were lower than preoperative period and 1 week postoperatively, and the quality of survival scores in 1 week postoperatively were higher than the preoperative period, and the differences were statistically significant (P<0.05). Conclusion The application of narrative nursing to lung cancer surgery patients is conducive to alleviating perioperative symptom clusters, helping patients achieve post-traumatic growth, and enhancing their psychosocial adaptability and quality of survival.